QUINOXALINE-2,3-DIONE: CHEMICAL STRUCTURE, SYNTHETIC STRATEGIES, STRUCTURE–ACTIVITY RELATIONSHIP, REACTIVITY, AND PHARMACOLOGICAL ACTIVITIES - Dr.K.Manisha; Mayank Bhartwaj; Akash Gautam; D. Venket Sai (Asian Journal of Pharmaceutical Research and Development, 2026)
Type 2 Diabetes Mellitus (T2DM) is increasingly being diagnosed among young individuals due to lifestyle changes and genetic predisposition. C-peptide, a by-product of insulin synthesis, serves as a reliable marker of endogenous insulin secretion and β-cell function. This study was conducted to evaluate the role of C-peptide estimation in newly diagnosed Type 2 diabetic patients. A prospective observational study was carried out on 200 patients aged 18–35 years. Data including fasting blood sugar, postprandial blood sugar, HbA1c, and C-peptide levels were collected and analyzed. The results showed that patients with higher C-peptide levels had better glycemic control, while those with lower levels required early insulin therapy. A negative correlation was observed between HbA1c and C-peptide levels. The study concludes that C-peptide estimation plays an important role in assessing β-cell function and guiding treatment strategies in young Type 2 diabetic patients.